THE INDUSTRIALIZATION OF THE QUR'AN IN INDONESIA - Ahmad Saifudin (STAI Syubbanul Wathon Magelang, 2018)
The Qur'an as a protected holy book (al-kitab al > -mahfu z> ) has crossed along historical journey. It is revealed as a reading text (al-matlu>), thanbe a writing text (al-maktub). The tradtion of Qur`anic wiriting >undergoes a very significant transformation; from traditional tomodern (printing). Based on data, the oldest Qur`anic printing inIndonesia is found in Palembang with the codecology 21 Ramadhan1264 H coinciding with 21 August 1848 M. This effort is done by alFaqir ila Allah Ta'ala al-Hajj Muhammad Azhari bin Kemas al-HajjiAbdullah. The effort to print the Qur'an can not be separated from therole of the company and the government. Both have their respectiveroles. In general, companies play a role in producing/printing anddistributing, while the government is more to the control function